Review of Botany, Nutritional, Medicinal, Pharmacological Properties and Phytochemical Constituents of Bruguiera gymnorhiza (L.) Lam, (Rhizophoraceae) - Collen Musara ,; Elizabeth Bosede Aladejana ,; Silas M. Mudyiwa, (Journal of Pharmacy and Nutrition Sciences, 2020)
Bruguiera gymnorhiza (L.) Lam, popularly known as black Mangroves, is an economical and valuable medicinal plant that is commonly found in relatively distinct zones, which are controlled by factors such as salinity, tidal regime, soil type and seed predators.This study is aimed at reviewing the botany, nutritional and medicinal uses, phytochemistry and pharmacological properties of B. gymnorhiza. A comprehensive literature search was done using electronic databases including journal articles, books, theses, scientific reports and internet sources.The most widespread direct use of B. gymnorhiza is for wood and other uses include food, medicines, dyes and environmental services. Different compounds such as β-sitosterol, α-amyrin, β-amyrin, ursolic acid, stigmasterol, lupeol, taraxerol, bruguierol, oleanolic acid, gymnorhizol, bruguiesulfurol, isobrugierol and ellagic acid have been isolated from B. gymnorhiza. The leaves, dried roots,stem and barks of B. gymnorhiza have shown the presence of flavonoids, phenols, hydroquinones, tannins, saponins, terpenoids, gums, reducing sugars,phenolic compounds, alkaloids, steroids, terpenoids and glycosides.These compounds are sterols and have shown high anti-inflammatory activity, antidiabetic, antioxidant and angiogenic effects, inducing apoptosis, hypocholesterolemic activity, anthelminthic and antimutagenic activities. B. gymnorhiza plant extract contains chemical constituents of pharmacological importance, which can play a significant role in the production of pharmaceutical products for future use.